Supramaximal Interval Running Prescription in Australian Rules Football Players: A Comparison Between Maximal Aerobic Speed, Anaerobic Speed Reserve, and the 30-15 Intermittent Fitness Test. Issue 12 (11th December 2022) - Collison, Jay; Debenedictis, Thomas; Fuller, Joel T.; Gerschwitz, Ryan; Ling, Tayla; Gotch, Lochlan; Bishop, Brenden; Sibley, Lauren; Russell, Jed; Hobbs, Amy; Bellenger, Clint R.
Abstract: Collison, J, Debenedictis, T, Fuller, JT, Gerschwitz, R, Ling, T, Gotch, L, Bishop, B, Sibley, L, Russell, J, Hobbs, A, and Bellenger, CR. Supramaximal interval running prescription in Australian Rules Football players: A comparison between maximal aerobic speed, anaerobic speed reserve and the 30-15 intermittent fitness test. J Strength Cond Res 36(12): 3409–3414, 2022—Accurate prescription of supramaximal interval running during Australian Rules Football (AF) preparatory periods is important to facilitate the specific targeting of physiological and neuromuscular adaptation. This study compared the variability in supramaximal interval running performance prescribed by proportion of maximal aerobic speed (MAS), anaerobic speed reserve (ASR), and 30-15 intermittent fitness test (30-15IFT) terminal speed. Seventeen male junior AF players first completed assessments of MAS, ASR, and 30-15IFT in a randomized order. They subsequently performed supramaximal interval running trials (15 seconds on: 15 seconds off until volitional exhaustion) at 120% MAS, 20% ASR, and 95% 30-15IFT in a randomized order. Variability in time to exhaustion (TTE) for each prescription method was calculated as the mean of the square root of the squared difference between the individual value and the mean value, and it was compared via repeated-measures analysis of variance with statistical significance set at p ≤ 0.05. Time to exhaustion during supramaximal interval running was not different between the prescription methods ( p = 0.58). Time to exhaustion residuals were reduced when prescribed by ASR compared with MAS (standardized mean difference [SMD] = −0.47; 29%); however, confidence intervals about this reduction indicated that there was some uncertainty in this finding (SMD = −1.03 to 0.09; p = 0.09). Trivial differences in TTE residuals were present when prescribed by 30-15IFT compared with MAS (SMD = −0.05 ± 0.59; p = 0.86). Although there was some uncertainty about the reduction in supramaximal interval running performance variability when prescribed by ASR compared with MAS, the 29% reduction exceeds the inherent error in TTE efforts (i.e., ∼9–15%) and may thus be considered practically meaningful. Reducing supramaximal interval running performance variability ensures similar physiological demand across individuals, potentially facilitating similar degrees of physiological adaptation.